A POLÍTICA DE CONTRA-REFORMA AGRÁRIA DO BANCO MUNDIAL NO CEARÁ - Oliveira, Alexandra Maria de (GEOUSP Espaço e Tempo (Online), 2006)
The article analyzes the agrarian credit policy in Ceará, put into practice by the State and Federal Governments in partnership with the World Bank since 1996. The reason which led the State government begin and develop the “market agrarian reform” in Ceará, puts back important problems: the agrarian reform problem and the land access to the landless peasantry, the agrarian structural problem in Ceará, in the Northeast. The reflection on the agrarian counter-reformation of Wold Bank passes by the discussion concerning the contradictory (unequal and combined) territorial development, developed inside the Agrarian Geography. The research was developed from a transversal study accomplished in eight settlements created from the São José and Cédula da Terra projects. The implementation of the “market agrarian reform” in Ceará, has meant the appropriation of the capitalized income of the land by landowners of the rentable land. The settlements as fractions of the conquered territory have been constituted based on the family property that is a property form different from the capitalist private property.